The awareness of education and the role of education orientation in rural Vietnam: the case of Hòa Phú Commune, Châu Thành District, Long An Province (Revista de Investigaciones Universidad del Quindío, 2023)
The study is to investigate and analyse the perception of parents in Hòa Phú Commune about education and their guidance toward their children’s career education orientation in the current period. The study is based on ethnographical fieldwork methodology with 29 in-depth interviews across all five hamlets (cluster sampling) and several observation journeys. The authors spent 3 years working at the research site. The child's continuing education depends largely on his or her own wishes. In fact, there is an interaction between the internal factors (parents' wishes, expectations and needs) and external factors (economic, cultural and social circumstances) of the educational orientation of children in rural families. In many cases, there is a gap between what parents think and what they act about their children's education. Local families rationally choose to guide and invest in their children's education. The research shows how contemporary Vietnamese rural residents view and position their children's education, especially the future vocational education.
Keywords: consciousness; education; family; rational choice; Long An Province